1981
DOI: 10.1073/pnas.78.5.3199
|View full text |Cite
|
Sign up to set email alerts
|

A spectrum of monoclonal antibodies reactive with human mammary tumor cells.

Abstract: Splenic lymphocytes of mice, immunized with membrane-enriched fractions ofmetastatic human mammary carcinoma tissues, were fused with the NS-1 non-immunoglobulinsecreting murine myeloma cell line. This resulted in the generation of hybridoma cultures secreting immunoglobulins reactive in solid-phase radioimmunoassays with extracts of metastatic mammary carcinoma cells from involved livers, but not with extracts ofapparently normal human liver. As a result offurther screening of immunoglobulin reactivities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
162
0
3

Year Published

1982
1982
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(166 citation statements)
references
References 11 publications
1
162
0
3
Order By: Relevance
“…Monoclonal antibodies have been produced against a number of human tumours, including melanoma (Dippold et al, 1980;Koprowski et al, 1978;Yeh et al, 1979), lung carcinoma (Kasai et al, 1981;Sikora & Wright, 1981), mammary carcinoma (Colcher et al, 1981;Schlom et al, 1980, Thompson et al, 1983, colorectal carcinoma (Herlyn et al, 1979;Koprowski et al, 1979) as well as other tumours (Deng et al, 1981;Kennett & Gilbert, 1979;Nadler ct al., 1980;Ritz et al, 1980;Sikora & Phillips, 1981;Ueda et al, 1981). The majority of these antibodies recognise either polymorphic, monomorphic or tissue-specific determinants, whilst others may recognise tumour-specific antigens, although this is questionable.…”
mentioning
confidence: 99%
“…Monoclonal antibodies have been produced against a number of human tumours, including melanoma (Dippold et al, 1980;Koprowski et al, 1978;Yeh et al, 1979), lung carcinoma (Kasai et al, 1981;Sikora & Wright, 1981), mammary carcinoma (Colcher et al, 1981;Schlom et al, 1980, Thompson et al, 1983, colorectal carcinoma (Herlyn et al, 1979;Koprowski et al, 1979) as well as other tumours (Deng et al, 1981;Kennett & Gilbert, 1979;Nadler ct al., 1980;Ritz et al, 1980;Sikora & Phillips, 1981;Ueda et al, 1981). The majority of these antibodies recognise either polymorphic, monomorphic or tissue-specific determinants, whilst others may recognise tumour-specific antigens, although this is questionable.…”
mentioning
confidence: 99%
“…In general, cultured malignant cell lines are being used to elicit and detect these antibodies. Although some of them appear to be tumour-specific at present (Colcher et al, 1981) many others have been found, on further study, to react with cells other than the tumour cell (Koprowski et al, 1978;Dippold et al, 1980;Brown et al, 1981). Clearly, testing the specificity of individual McAbs, particularly for crossreactions with normal tissue, is of the utmost importance prior to their use in clinical situations: e.g.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The MAb B72.3 IgG was generated using a membrane-enriched fraction from a mammary carcinoma metastasis. 35 The MAbs CC49 and B72.3 were purified from ascitic fluid obtained from pristaneprimed BALB/c mice. The resulting ascitic fluid was diluted 1:1 with 20 mM sodium phosphate, pH 7.0 and loaded on a Protein G Sepharose 4 Fast Flow column (Pharmacia, Piscataway, NJ).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%